Systems analysis and synthesis : bridging computer science and information technology - Dwyer, Barry (San Francisco : Morgan Kaufmann Publishers is an imprint of Elsevier, 2016)
Systems Analysis and Synthesis: Bridging Computer Science and Information Technology presents several new graph-theoretical methods that relate system design to core computer science concepts, and enable correct systems to be synthesized from specifications. Based on material refined in the author's university courses, the book has immediate applicability for working system engineers or recent graduates who understand computer technology, but have the unfamiliar task of applying their knowledge to a real business problem. Starting with a comparison of synthesis and analysis, the book explains the fundamental building blocks of systems--atoms and events--and takes a graph-theoretical approach to database design to encourage a well-designed schema. The author explains how database systems work--useful both when working with a commercial database management system and when hand-crafting data structures--and how events control the way data flows through a system. Later chapters deal with system dynamics and modelling, rule-based systems, user psychology, and project management, to round out readers' ability to understand and solve business problems. Bridges computer science theory with practical business problems to lead readers from requirements to a working system without error or backtrackingExplains use-definition analysis to derive process graphs and avoid large-scale designs that don't quite workDemonstrates functional dependency graphs to allow databases to be designed without painful iterationIncludes chapters on system dynamics and modeling, rule-based systems, user psychology, and project management.
Print version record.
Includes index.
Keywords: System design; Graph theory; SCIENCE -- System Theory; TECHNOLOGY & ENGINEERING -- Operations Research; Graph theory; System design; Electronic books